Mapping Music Education Research in Brazil and Argentina: The British Impact - Hentschke, Liane (2004)
In this brief article we share with our colleagues around the world the British impact on the development of music education and psychology of music research in Brazil and Argentina. Although both countries are pursuing similar research policies, their research areas differ. Brazilian research on music education has had its focus on curriculum studies, evaluation, psychology of music, and media studies. Argentina on the other hand has a strong tradition in research in music education and psychology of music, in particular developmental and cognitive aspects of music perception and performance. Both countries are working towards the improvement of music research in South America and the continuation of the fertile partnership with British scholars and institutions.